Intertextual and intermedial elements in the formation of identity of the characters in Almodovar’s film "High heels" - Varga, Dejan (Anafora, 2022)
The category of identity is the fundamental framework of the paper that contains a brief overview of the theoretical constructs of personal identity and interprets mechanisms by which it is formed. The main part of the paper includes an analysis of the identity of characters that appear in the film High Heels (1991) of the contemporary Spanish director Pedro Almodóvar. The character identities present a very clear view of what contemporary literary theory describes as an antiessential approach towards creating a person’s identity. In his films, Almodóvar used numerous mechanisms for such an approach to these issues, and in the chosen film paradigm the intertextual and intermedial approaches have proven to be key moments that emphasize that the formation of a person’s identity rests on the necessary interactions with the other.